2009
DOI: 10.1111/j.1525-1594.2008.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression During the Formation of Bioengineered Heart Muscle

Abstract: A three-dimensional bioengineered heart muscle (BEHM) construct model had been previously developed, exhibiting contractile forces up to 800 microN. The interest of this study was to determine gene expression levels of biologic markers involved in calcium-handling between BEHM, cell monolayer, and neonatal heart. Cardiac cells were isolated from one litter of F344 rats and organized into groups (n = 5): 4-, 7-, 10-day BEHM and cell monolayer; BEHM was evaluated for cell viability and contractility. Groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In this study, we have shown the differing effects following the manipulation of e-, α- or βMYH in both the atria and ventricle at early stages of heart development, which might result in alterations between the generation of the electrical activity of the cells and their Ca 2+ transients. These Ca 2+ transient changes are fundamental to proper activation of the machinery of contraction, in which MYH plays a key role (Chandra et al, 2007; Dillmann, 2009; Khait and Birla, 2009), but also to the regulation of gene expression (Webb and Miller, 2003). Evidence is presented suggesting that eMYH has a major impact on the AP properties of the atrial and ventricular cells, with AP characteristics that are normally found during very early heart development (Arguello et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown the differing effects following the manipulation of e-, α- or βMYH in both the atria and ventricle at early stages of heart development, which might result in alterations between the generation of the electrical activity of the cells and their Ca 2+ transients. These Ca 2+ transient changes are fundamental to proper activation of the machinery of contraction, in which MYH plays a key role (Chandra et al, 2007; Dillmann, 2009; Khait and Birla, 2009), but also to the regulation of gene expression (Webb and Miller, 2003). Evidence is presented suggesting that eMYH has a major impact on the AP properties of the atrial and ventricular cells, with AP characteristics that are normally found during very early heart development (Arguello et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Further, as seen with αMHC, the atrial and ventricular cardiomyocytes had normal action potentials, although irregular Ca 2+ transients were seen in atrial and ventricular cells [42]. Defects in calcium signaling may lead to defects in contraction of the heart, with MHC known to be important for induction of contraction [6769]. Two fish models have been used to analyze the presumptive functional orthologue to MYH7 .…”
Section: The Myosin Heavy Chains and The Cardiovascular Systemmentioning
confidence: 99%
“…Luda Khait and Ravi K. Birla (110) of the University of Michigan, Ann Arbor, MI, USA evaluated changes in gene expression during the formation of bioengineered heart muscle (BEHM). Cardiac cells were isolated from one litter of F344 rats and organized into the groups 4‐, 7‐, 10‐day BEHM and cell monolayer.…”
Section: Tissue Engineeringmentioning
confidence: 99%